2013
DOI: 10.1097/mao.0b013e3182804949
|View full text |Cite
|
Sign up to set email alerts
|

UHV-Alginate as Matrix for Neurotrophic Factor Producing Cells—A Novel Biomaterial for Cochlear Implant Optimization to Preserve Inner Ear Neurons From Degeneration

Abstract: This study demonstrates UHV-alginate to be a suitable scaffold for BDNF-producing fibroblasts. UHV-alginates are a promising biomaterial for cochlear implant biofunctionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…Despite this, the supernatant including the cell‐delivered BDNF did have an equal or even better neuroprotective effect than the recombinant BDNF. A similar finding was observed when investigating the neuroprotective effect of BDNF overexpressed from genetically modified NIH3T3 fibroblasts (Hütten et al, ). There, fibroblasts produced BDNF in concentrations in the picogram range but the neuroprotective effect was significantly increased compared to the relevant control (recombinant human BDNF 50 ng/ml).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Despite this, the supernatant including the cell‐delivered BDNF did have an equal or even better neuroprotective effect than the recombinant BDNF. A similar finding was observed when investigating the neuroprotective effect of BDNF overexpressed from genetically modified NIH3T3 fibroblasts (Hütten et al, ). There, fibroblasts produced BDNF in concentrations in the picogram range but the neuroprotective effect was significantly increased compared to the relevant control (recombinant human BDNF 50 ng/ml).…”
Section: Discussionsupporting
confidence: 82%
“…To enhance the therapeutic effect achievable with MSCs we here developed a lentivirally based system for BDNF‐overexpression and secretion by human mesenchymal stem cells (hMSCs). The transplantation of BDNF‐overexpressing hMSCs should be linked to a delivery system avoiding cell migration and allowing nutrition and growth factor diffusion such as encapsulated cell devices (Konerding et al, ; Wahlberg et al, ) or hydrogel entrapment (Hütten et al, ). For this purpose, it may be beneficial to differentiate the hMSC into chondrocytes: firstly, differentiated cells are less carcinogenic or tumorigenic, and secondly, chondrocytes are able to withstand hypoxic conditions and low nutrient supply.…”
Section: Introductionmentioning
confidence: 99%
“…Using ultra-high viscous alginate (UHV-alginate) made of the brown algal species Lessonia nigrescens and Lessonia trabeculata , it has been shown that coating the CI with this alginate is possible (Schwieger et al, 2018). It has also been demonstrated that BDNF-overexpressing murine fibroblasts survive in the UHV-alginate and release BDNF at a concentration that is neuroprotective in vitro (Hütten et al, 2013). Since gaining approval for use in humans of murine fibroblasts as xenogeneic cells may be difficult, a human cell source may prove more beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other studies with cell-based drug delivery, 15,33,43,44,61,62 the tested MSCs have the great advantage of being an autologous source. MSCs can be obtained, modified, and encapsulated from patients before they undergo a cochlear implantation.…”
Section: Amount and Biological Effect Of Released Bdnfmentioning
confidence: 96%
“…30,31 Furthermore, a bidirectional transfer of small molecules is possible, leading to a supply with nutrients, growth factors, and oxygen. At the same time, waste products, CO 2 , and produced active molecules, such as insulin 32 or BDNF, 33 can be released. For biotechnological processes, alginate lyases allow the defined degradation of the liquid and gelled alginates.…”
Section: Introductionmentioning
confidence: 99%